Cardiac autonomic regulation during exposure to auditory stimulation with classical baroque or heavy metal music of different intensities - Amaral, Joice Anaize Tonon do [UNESP]; Nogueira, Marcela Leme [UNESP]; Roque, Adriano L. [UNESP]; Guida, Heraldo Lorena [UNESP]; Abreu, Luiz Carlos de; Raimundo, Rodrigo Daminello; Vanderlei, Luiz Carlos Marques [UNESP]; Ribeiro, Vivian F.; Ferreira, Celso; Valenti, Vitor Engrácia [UNESP] (Turkish Society of Cardiology, 2014)
Objectives: The effects of chronic music auditory stimulation on the cardiovascular system have been investigated in the literature. However, data regarding the acute effects of different styles of music on cardiac autonomic regulation are lacking. The literature has indicated that auditory stimulation with white noise above 50 dB induces cardiac responses. We aimed to evaluate the acute effects of classical baroque and heavy metal music of different intensities on cardiac autonomic regulation. Study design: The study was performed in 16 healthy men aged 18-25 years. All procedures were performed in the same soundproof room. We analyzed heart rate variability (HRV) in time (standard deviation of normal-to-normal R-R intervals [SDNN], root-mean square of differences [RMSSD] and percentage of adjacent NN intervals with a difference of duration greater than 50 ms [pNN50]) and frequency (low frequency [LF], high frequency [HF] and LF/HF ratio) domains. HRV was recorded at rest for 10 minutes. Subsequently, the volunteers were exposed to one of the two musical styles (classical baroque or heavy metal music) for five minutes through an earphone, followed by a five-minute period of rest, and then they were exposed to the other style for another five minutes. The subjects were exposed to three equivalent sound levels (60- 70dB, 70-80dB and 80-90dB). The sequence of songs was randomized for each individual. Results: Auditory stimulation with heavy metal music did not influence HRV indices in the time and frequency domains in the three equivalent sound level ranges. The same was observed with classical baroque musical auditory stimulation with the three equivalent sound level ranges. Conclusion: Musical auditory stimulation of different intensities did not influence cardiac autonomic regulation in men.